Changes in management accounting, innovation and person job fit practices in Lembaga Zakat Selangor / Sharifah Norzehan Syed Yusuf - Syed Yusuf, Sharifah Norzehan (2011)
Zakat Institutions are bodies that exist in Muslim societies, where their functions are similar to an Inland Revenue department on the one hand and a social welfare organization on the other. The core activities of zakat institutions are collecting compulsory donations from eligible Muslims and distributing them to the rightful beneficiaries. These organizations provide various kinds of assistance such as food, shelter, health and education to rightful beneficiaries. With many resources to safeguard, zakat bodies need to enhance their management systems to avoid negligence or misuse of funds. Realising the importance of enhancing their management systems zakat bodies in Malaysia initiated several changes in their management practices. This thesis studies changes in MAS, Innovation and Person Job Fit practices and their roles in enhancing zakat management. The thesis uses qualitative case study research methods to understand the phenomena of changes in Lembaga Zakat Selangor. LZS was formed as a result of public management reforms and corporatisation and has now existed for more than ten years. Other zakat institutions have not undergone full public management reform. Selangor State is the only state that has undergone reforms resulting in a zakat institution operating both zakat collection and distribution (LZS). Some of the changes that have taken place in Lembaga Zakat Selangor were found to be successful and some are not.